Five autoantibodies identified from immune complexes as breast cancer biomarkers - Zheng, Ningwei; Li, Yueqi; Peng, Zhengke; Tang, Yaolin; Liang, Zhiqiang; Wang, Hong; Dai, Hong; Tan, Gongjun (Frontiers in Immunology, 2025)
ObjectiveComprehensive identification and profiling of antigens in serum immune complexes (ICs) is crucial for developing early diagnostic biomarkers for cancer. We therefore undertook this study to identify novel IC-derived autoantigens and autoantibodies in patients with breast cancer, and to evaluate their potential as new biomarkers.MethodsICs were purified from serum with C1q and Protein A/G affinity capture. The isolated complexes were digested with papain and analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Twelve candidate autoantibodies revealed by LC-MS/MS were first verified with a digital liquid chip method (DLCM) in baseline serum from 40 breast cancer patients and eight healthy controls. Five autoantibodies were then validated in independent cohorts of 33 breast cancer patients and 45 healthy controls, using DLCM.ResultsAutoantibodies targeting PF4, PSMB3, PRPF19, RTCB, SDHA, ENO1, PTBP2, PRDX6, ANP32A, VDAC1, MMP14 and HSPA4 were identified both purification methods. In the verification cohort, IgG autoantibodies against HSPA4, ENO1, PRDX6, PRPF19 and MMP14 were significantly increased in breast cancer patients with areas under the curve (AUCs) of 0.90, 0.89, 0.82, 0.78 and 0.77, respectively. Their combined panel discriminated breast cancer from controls with an AUC of 0.97. In the validation cohort, the same autoantibodies achieved AUCs of 0.79, 0.81, 0.73, 0.87, and 0.82, and the combination of these five autoantibodies yielded an AUC of 0.88.ConclusionsThe autoantibodies identified from ICs can serve as effective serum biomarkers for breast cancer. Anti-HSPA4, anti-PRPF19, anti-ENO1, anti-PRDX6, and anti-MMP14 autoantibodies showed significant increases in breast cancer patients.